2012
DOI: 10.1590/s1516-35982012000100009
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of body biometrics during growth of elite Santa Ines sheep

Abstract: -The objective of this study was to characterize body biometrics of Santa Ines sheep during growth. Data from 4,038 animals, males and females, with ages from four to 36 months, from different herds participating in the National Agricultural Fair in Bahia from 2003 to 2008 were used. The characteristics evaluated were: body weight, average daily gain, body length, thoracic circumference, anterior height and posterior height. The mean values found were compared by the Student-NewmanKeuls test. All characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…These results demonstrate the viability of farming meat sheep using those cultivars. Studies involving Santa Inês rams and ewes also reported that these animals reached 70% of adult weight at 360 to 450 days of age [31]. The current results agree with the statement that Santa Inês is for meat production.…”
Section: Resultssupporting
confidence: 89%
“…These results demonstrate the viability of farming meat sheep using those cultivars. Studies involving Santa Inês rams and ewes also reported that these animals reached 70% of adult weight at 360 to 450 days of age [31]. The current results agree with the statement that Santa Inês is for meat production.…”
Section: Resultssupporting
confidence: 89%
“…Thus, differences may occur among animals under different nutritional managements or ages. Studies using traditional morphometry in domestic animal species have found variations among populations of different herds or locations, considering the body measurements of these animals (Yakubo et al, 2010;Ogah et al, 2011;Texeira-Neto et al, 2012;). However, it is difficult to say whether the variation found is due to differences between individuals or environmental effects.…”
Section: Discussionmentioning
confidence: 99%